Bolted and welded connectors for the rehabilitation of composite beams. (October 2016) - Pathirana, Sameera Wijesiri; Uy, Brian; Mirza, Olivia; Zhu, Xinqun
Abstract: Recent research studies revealed that blind-bolts can be used to strengthen existing composite steel-concrete beams more efficiently and effectively than welded stud connectors. In the general retrofitting operation procedure, the holes created in the concrete slab of composite beams to fix shear connectors are finally backfilled with grout. However, it is clear from a review of the open literature that very few studies have been conducted on the behaviour of shear connectors in grout in retrofitted composite beams. This paper investigates the load-slip behaviour of blind-bolt and welded stud connectors in grout under retrofitted conditions both experimentally and numerically. A series of push-out test experiments was carried out based on the Eurocode 4. The behaviour of retrofitted push-out test specimens during the testing was simulated using Finite Element (FE) models. The concrete and grout properties were modelled by specifying damage criteria using the concrete damage plasticity (CDP) option available in ABAQUS. The effects of height:diameter ratio of the connectors and grout strength on the shear capacity of blind-bolt and welded stud connectors were verified using parametric FE analyses. A modified design equation was proposed to estimate the ultimate shear capacity of bolted connectors in grout. The shear connector properties such as shear resistance, stiffness, ductility and failure modes have been compared and discussed in detail by using the experimental and FE results. These results provide an extended understanding of the feasibility of utilising blind-bolts for retrofitting substandard composite beams. Highlights: Load-slip behaviour of blind-bolt and welded stud connectors in grout under retrofitted conditions was tested both experimentally and numerically. A series of push-out test experiments was carried out based on the Eurocode 4. The behaviour of retrofitted push-out test specimens during the testing was simulated using Finite Element (FE) models. The concrete and grout properties were modelled by specifying damage criteria using the concrete damage plasticity (CDP) option available in ABAQUS. The effects of height:diameter ratio of the connectors and grout strength on the shear capacity of blind-bolt and welded stud connectors were verified using parametric FE analyses. A modified design equation was proposed to estimate the ultimate shear capacity of bolted connectors in grout.